2022
DOI: 10.3390/su14095250
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Communities in Adaptation to Climate Change by Understanding the Dimensions of Social Capital in Atlantic Canada

Abstract: This paper examines the role of social capital and its influence on the capacity of coastal communities in Atlantic Canada to respond and adapt to climate change, especially when dealing with extreme weather events. Three elements of social capital—social trust, institutional trust, and social networks—were considered. They were analyzed based on four questions targeting social capital during semi-structured interviews on climate change adaptation in 10 rural coastal communities located in three Canadian provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Climate change refers to long-term changes in temperature and weather patterns, which are caused principally by the global warming potential of fossil fuel emissions. [14,15]. Changing temperatures, shifting seasons, precipitation patterns, intensity/frequency of extreme weather events, coastal erosion resulting from storm surges, and ocean acidification are all impacts of climate change that will bring vulnerabilities to the tourism industry of PEI [16].…”
Section: Climate Change Impacts On Tourismmentioning
confidence: 99%
“…Climate change refers to long-term changes in temperature and weather patterns, which are caused principally by the global warming potential of fossil fuel emissions. [14,15]. Changing temperatures, shifting seasons, precipitation patterns, intensity/frequency of extreme weather events, coastal erosion resulting from storm surges, and ocean acidification are all impacts of climate change that will bring vulnerabilities to the tourism industry of PEI [16].…”
Section: Climate Change Impacts On Tourismmentioning
confidence: 99%
“…Author Proposal Henry and Vollan (2014) An approach for linking sustainability knowledge with action, in a way that enhances collective actions and promotes active social learning using OSNs Bakht et al (2018) An approach that fosters the use of sustainable urban systems using OSNs G omez-Mar ın et al (2022) An approach that fosters the promotion of sustainable Research and Development Projects, efficient management of knowledge, resources and dynamics of the stakeholders, and implements a sustainable long-term plan using OSNs Atstaja et al (2022) An approach to use OSNs to foster sustainable decision-making for raising finance, develop sharing economy, and create environment-friendly trends Seo et al (2017) An approach to teach the central concepts of sustainable development using OSNs Henry (2009) An approach to achieve successful learning of sustainability using OSNs Ungar and Strand (2012) An approach for the co-production of biological and cultural knowledge for decision-making using OSNs Vasseur et al (2022) An approach to examine the role of social capital to respond and adapt to climate change, especially when dealing with extreme weather events Beyers and Leventon (2021) An approach to assess a multi-stakeholder initiative to provide spaces for sustainability learning transformation Henry (2020) An approach to examine the effect of organizations' different policies in sustainability learning Wojcik et al (2021) An approach to analyze how environmental learning occurs Lam et al (2021) An approach to foster fundamental societal change and increase the impact of local actors' sustainability initiatives Shaharudin et al (2019) Garcia et al (2020) A method to establish strategies for sustainability initiatives in OSNs Smith and Sharicz (2013) A method to use OSNs to promote sustainability inside organizations Baggio and Hillis (2018) A method to assess the success of the sustainability initiatives in OSNs Hamann ( 2009 A method to allow companies to make a positive contribution to sustainable development using OSNs Strasser et al (2019) A method for managing the role of leaders that act as agents to promote transformative changes for sustainability Groce et al (2019) A method to use OSNs for environmental awareness LaMendola (2019)…”
Section: Contributions To the Theorymentioning
confidence: 99%
“…Two main research gaps must be filled to efficiently use OSNs for sustainability awareness and advance the state-of-the-art in this body of knowledge. First, in the literature, scholars have explored how different factors, tools and approaches affect the success of sustainability awareness through OSNs (Chou and Huang, 2021;Sysoieva and Osadcha, 2020); proposed new methods, theoretical frameworks and approaches (Vasseur et al, 2022;Al-Marghilani, 2022); and showed different case examples (Bellantuono et al, 2022;Hurajova et al, 2022). The contributions of these studies should be considered in designing and developing OSNs and sustainability initiatives using OSNs.…”
Section: Introductionmentioning
confidence: 99%
“…The average in years of experience in milk production was 21.32, which could have a direct relationship with a higher economic income [42] but could not be related to sustainable cattle farms from social, environmental, and governance perspectives [43]. Regarding advice from community leaders, 96.18% of livestock farmers indicated that they do not receive this benefit, which prevents the formation of networks needed to improve adaptive governance and social cohesion [44]. Therefore, advice, as a social process among people at a local level, is necessary as it helps to improve a community's capacity to adapt to CC [45].…”
Section: Relationship Between Dairy Farmers' Livelihoods and Percepti...mentioning
confidence: 99%